ENERGY AUDIT ON LIGHTING AND AIR CONDITIONING SYSTEMS AT AL-AZHAR ISLAMIC SCHOOL - Khabaranus, Yusvian; Purwoharjono, Purwoharjono; Gianto, Rudy (Faculty of Engineering, Universitas Tanjungpura, 2023)
Based on Government Regulation No. 70 of 2009 concerning energy conservation, it is stated that the use of energy by energy sources and users must be carried out sparingly and efficiently. Based on these regulations, this thesis was made with the aim of analyzing opportunities for saving electrical energy in the Islamic Middle School Al-Azhar 17 Pontianak and Islamic High School Al-Azhar 10 Pontianak buildings. Data collection was carried out from December 2022 to January 2023. The results of the analysis obtained 2 recommendations for saving electricity. In the first option, for the lighting system it is done by changing TL lamps to LEDs, requiring 240 LED lamps and for the air conditioning system it is done by changing the refrigerant to Musicool MC-22. Estimated electricity savings of 17%. The payback period is 2 years, 3 months. In the second option, 446 LED lamps were also replaced with TL lamps to LEDs. For the air conditioning system, the AC is replaced with an inverter type. Estimated electricity savings of 61.13%. The payback period is 2 years, 2 months. From the results of this analysis, energy conservation efforts to get electricity savings and cost savings are very feasible in these schools.